Clinical utility of endoscopic ultrasound-guided tissue acquisition for comprehensive genomic profiling of patients with biliary tract cancer, especially with intrahepatic cholangiocarcinoma - Takafumi Yanaidani; Kazuo Hara; Nozomi Okuno; Shin Haba; Takamichi Kuwahara; Yasuhiro Kuraishi; Nobumasa Mizuno; Sho Ishikawa; Masanori Yamada; Tsukasa Yasuda (Korean Society of Gastrointestinal Endoscopy, 2024)
Background/Aims Endoscopic ultrasound-guided tissue acquisition (EUS-TA) is a standard diagnostic method for biliary tract cancer (BTC), and samples obtained in this manner may be used for comprehensive genomic profiling (CGP). This study evaluated the utility of EUS-TA for CGP in a clinical setting and determined the factors associated with the adequacy of CGP in patients with BTC. Methods CGP was attempted for 105 samples from 94 patients with BTC at the Aichi Cancer Center, Japan, from October 2019 to April 2022. Results Overall, 77.1% (81/105) of the samples were adequate for CGP. For 22-G or 19-G fine-needle biopsy (FNB), the sample adequacy was 85.7% (36/42), which was similar to that of surgical specimens (94%, p=0.45). Univariate analysis revealed that 22-G or larger FNB needle usage (86%, p=0.003), the target primary lesions (88%, p=0.015), a target size ≥30 mm (100%, p=0.0013), and number of punctures (90%, p=0.016) were significantly positively associated with CGP sample adequacy. Conclusions EUS-TA is useful for CGP tissue sampling in patients with BTC. In particular, the use of 22-G or larger FNB needles may allow for specimen adequacy comparable to that of surgical specimens.